Analisis Efektivitas Dan Efisisensi Layanan Penyampaian Surat Keberatan Secara Online (E-Objection) Pada Kantor Pelayanan Pajak Pratama Menteng Dua - Nursyifa Syawaliyah; Dian Wahyudin (Jurnal Ilmu Administrasi Publik, 2022)
E-objection is a form of tax modernization through the use of information technology which aims to make the delivery of objection letters   more   flexible,   fast,   safe   and   practical.   Utilization   of information technology in taxation is expected to improve services to taxpayers, in terms of success, satisfaction, time, cost and effort to be more effective and efficient. The purpose of this research is to analyze the effectiveness and efficiency as well as the constraints and driving entities of e-objection services at the Primary Tax Office of Menteng Dua. The research method used was a qualitative method with data collection techniques in the form of interviews, observations and literature studies. The results of this study indicate that the e-objection service at the Primary Tax Office of Menteng Dua is quite effective and efficient. Its effectiveness is seen in the success of the program and  targets,  satisfaction  with the program,  the  level  of  input  and output and the achievement of overall goals. Its efficiency is seen in time, cost and effort. On the other hand, DGT's central network/server disruption, unregistered letter numbers and low public understanding are obstacles in the e-objection service. However, the Primary Tax Office of Menteng Dua always tries to find solutions to overcome them, for example by carrying out regular maintenance and update.